2011
DOI: 10.1038/cr.2011.53
|View full text |Cite
|
Sign up to set email alerts
|

Host-viral effects of chromatin assembly factor 1 interaction with HCMV IE2

Abstract: Chromatin assembly factor 1 (CAF1) consisting of p150, p60 and p48 is known to assemble histones onto newly synthesized DNA and thus maintain the chromatin structure. Here, we show that CAF1 expression was induced in human cytomegalovirus (HCMV)-infected cells, concomitantly with global chromatin decondensation. This apparent conflict was thought to result, in part, from CAF1 mislocalization to compartments of HCMV DNA synthesis through binding of its largest subunit p150 to viral immediate-early protein 2 (IE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…et al , reported that histone H1.4 phosphorylation at S35, a variant of H1.2, seems to be necessary for maintaining proper mitotic chromatin structure such as chromatin decondensation [49]. Viruses have been shown to increase nuclear size and result in chromatin decondensation [50,51], these effects are consistent with the changes in H1 phosphorylation induced by adenovirus we observe here.…”
Section: Insight Into Histone Phosphorylation Sitessupporting
confidence: 90%
“…et al , reported that histone H1.4 phosphorylation at S35, a variant of H1.2, seems to be necessary for maintaining proper mitotic chromatin structure such as chromatin decondensation [49]. Viruses have been shown to increase nuclear size and result in chromatin decondensation [50,51], these effects are consistent with the changes in H1 phosphorylation induced by adenovirus we observe here.…”
Section: Insight Into Histone Phosphorylation Sitessupporting
confidence: 90%
“…compared to WT and Rev-Q548R IE2 genome replication ( Fig. 2A), which could possibly be explained by the recent transfection-based evidence that Q548R IE2 86 cannot bind to the chromatin assembly factor 1 protein p150 (16). However, the large increases in viral DNA levels between 24, 72, and 96 h p.i.…”
Section: Discussionmentioning
confidence: 58%
“…This indicates that other variables, such as high levels of transcription or blockage of sites by other proteins or complexes, influence IE2 occupancy. Previous immunofluorescence studies of IE2 in HCMV-infected cells suggested that IE2 predominantly localizes to the viral replication compartment in late infection and is enriched near viral genomes at PML bodies even prior to replication onset ( 37 , 77 , 78 ). This localization was also dependent on the ability of IE2 to bind DNA ( 37 ).…”
Section: Discussionmentioning
confidence: 99%